Scratch-resistant transparent decorating part material and preparation method thereof
By adding anti-scratch agents and surfactants to polycarbonate materials, and using high mixer and twin-screw extruder processes, the problem that transparent decorative parts made of polycarbonate materials are susceptible to scratches is solved, achieving It combines high transparency and scratch resistance, improving product quality and production efficiency.
Patent Information
- Application Number
- CN202411682291.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-21
AI Technical Summary
Transparent decorative parts prepared by polycarbonate materials are susceptible to scratches, resulting in a decrease in product quality and reduced production efficiency. It is difficult for the prior art to improve scratch resistance while maintaining high transparency.
By adding a scratchrine, surfactant, blocked phenolic antioxidant, and phosphate antioxidants to the polycarbonate material, and the process of mixing grains through high mixture mixed and double screw extruders , Improve the surface hardness of the material and reduce the friction coefficient, and coordinate the paddle resistance of transparent decorative parts.
While maintaining high transparency and low mist, it significantly improves the injury resistance of transparent decoration parts, improves the product's qualification rate and user experience, simplifies the production process and improves production efficiency.
Smart Images

Figure CN119331404A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of transparent decorative parts, and in particular to a scratch-resistant transparent decorative part material and a preparation method thereof. Background Art
[0002] With the continuous progress of material life, the public's aesthetic requirements for product appearance are getting higher and higher. As a unique visual experience, transparent design allows users to intuitively see the internal structure of objects, which greatly enriches the user's experience. This visual sense of transparency not only enhances the beauty of the product, but also increases the product's sense of technology and modernity. Therefore, transparent design has been widely used in various products, especially in high-end consumer electronics, home appliances, toys and other fields. Among many transparent materials, polycarbonate (PC) materials are favored for their unique transparency. Polycarbonate material is the only transparent material among the five major engineering plastics, and its own light transmittance is as high as 90%, which is much higher than other transparent materials. Therefore, polycarbonate materials are widely used in the preparation of transparent decorative parts in the fields of air conditioners, mobile phones, toys, etc. However, the hardness of polycarbonate materials themselves is relatively low, which brings a series of problems in practical applications. As appearance parts, transparent decorative parts have extremely high surface quality requirements. At the product manufacturing end, transparent decorative parts usually need to be covered with a protective film after molding, and even special protective equipment is used to prevent scratches, bumps and other undesirable phenomena during transportation and assembly. Despite these measures, in actual operation, transparent decorative parts are still susceptible to scratches and bruises, resulting in reduced quality and production efficiency of the final product. This has become an industry pain point on the manufacturing side. On the product user side, transparent decorative parts also face many problems in actual use. When users use the product in daily life, transparent decorative parts are easily scratched, especially in areas that are frequently touched. As the use time increases, the transparent effect gradually decreases, seriously affecting the user experience. For example, scratches on the mobile phone screen not only affect the appearance, but may also cause the touch screen function to fail; scratches on the air conditioner panel reduce the overall texture of the product and affect the user's willingness to buy.
[0003] In order to improve the scratch resistance of transparent decorative parts made of polycarbonate materials, in actual industry, a surface treatment process can be used to add a coating or coat a material with higher hardness on its surface. For example, Chinese patent CN219727508U discloses a highly transparent scratch-resistant polycarbonate film, which improves its scratch resistance through a siloxane hardening layer and a polyvinyl alcohol anti-scratch layer, but this process is relatively complicated and will reduce the production efficiency of the product. Therefore, if the hardness or scratch resistance of the transparent decorative material itself can be improved, scratch-resistant transparent decorative parts can be prepared more conveniently. Chinese patent CN108976745A discloses a scratch-resistant highly transparent polycarbonate composite material and a preparation method thereof, which uses nanowires treated with a titanate coupling agent or a silane coupling agent to improve the scratch resistance, but only qualitatively tests its scratch resistance, and there is a problem of complex surface treatment of the nanowires. Chinese patent CN106589880A discloses a transparent, low-temperature-resistant and scratch-resistant polycarbonate composite material. Compounding 100 parts of surface hardness improver H881 and 50 parts of nano anti-scratch masterbatch can make the surface pencil hardness of PC reach 2H, but its haze decreases significantly. Summary of the invention
[0004] The present invention aims to provide a scratch-resistant transparent decorative material and a preparation method thereof, aiming to improve the scratch resistance of a decorative strip while maintaining its high transparency.
[0005] To achieve the above object, the present invention adopts the following technical scheme: a scratch-resistant transparent decorative material, which comprises, by weight, 97.2 to 98.5 parts of polycarbonate, 1 to 2 parts of a scratch-resistant agent, 0.3 to 0.6 parts of a surfactant, and 0.2 parts of an antioxidant, wherein the antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant.
[0006] Preferably, as an improvement, the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:(0.5-2).
[0007] Preferably, as an improvement, the scratch-resistant agent is a mixture of a low-molecular-weight micropowder microcrystalline compound and a bio-based acid ester modified substance.
[0008] Preferably, as an improvement, the addition amount of the bio-based acid ester modification is 10%.
[0009] Preferably, as an improvement, the hindered phenol antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acrylonitrile, β-(4-hydroxyphenyl-3,5-di-tert-butyl)propionate, and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, and the phosphite antioxidant is at least one of tris[2.4-di-tert-butylphenyl]phosphite and bis(2.4-di-tert-butylphenyl)pentaerythritol diphosphite.
[0010] Preferably, as an improvement, the surfactant is a mixture of macromolecular stearates.
[0011] Preferably, as an improvement, a method for preparing a scratch-resistant transparent decorative material comprises the following steps:
[0012] Step 1: adding polycarbonate material, scratch resistance agent, surfactant, hindered phenol antioxidant and phosphite antioxidant into a high speed mixer and mixing;
[0013] Step 2, adding the obtained mixture into a twin-screw extruder for blending and granulation;
[0014] Step 3: Dry the prepared material to obtain a scratch-resistant transparent decorative piece.
[0015] Preferably, as an improvement, in step one, the mixing time is 5 minutes; in step two, the temperature of the twin-screw extruder is 230-260° C., and the screw speed is 400 rpm.
[0016] Preferably, as an improvement, in step three, the drying temperature is 100° C. and the drying time is 4 hours.
[0017] The principle and advantages of this solution are: in actual application, in this technical solution, the inventor conducts a reverse analysis of the reasons for the problem that the high transparency and scratch resistance of transparent decorative materials in the prior art cannot be taken into account at the same time: high-transparency and scratch-resistant transparent decorative materials need to add as low a content of functional additives as possible. Conventional scratch-resistant additives will affect transparency, and a single additive often has limited improvement on scratch resistance and requires a larger addition amount. Increasing the dosage of the additive will further reduce the transparency of the material, resulting in the need for special protection for transparent decorative parts during industrial production, which is also a major technical pain point in the industry. Based on this, the inventor proposed a formula for transparent decorative materials and a new method for preparation: First, in terms of material composition, this solution improves the scratch resistance of transparent decorative materials by synergistically considering both increasing the surface hardness of the material and reducing the surface friction coefficient of the material. In terms of increasing surface hardness: by optimizing the scratch-resistant agent, the hardness of the polycarbonate material is increased; in terms of reducing the surface friction coefficient of the material: by adding surfactants and optimizing their types, the surfactant is a mixture of macromolecular stearates, which can migrate to the surface of the product after processing to improve the surface lubrication performance, thereby reducing the surface friction coefficient of transparent decorative parts. Under the synergistic effect of the two, the scratch resistance can be improved at a lower content, and high transparency is maintained in the visible light range of 400-700nm. Secondly, in terms of preparation technology, PC resin and synergistic functional additives are melt-blended to prepare transparent decorative materials, which has the advantages of simple operation and easy mass production. Further, the scratch-resistant transparent decorative parts molded by conventional injection molding have a higher surface hardness and a lower friction coefficient, which can greatly improve the product's qualification rate at the manufacturing end and the user's experience comfort. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the light transmittance of the scratch-resistant material of Example 1-2 of the present invention within the wavelength range of 400 to 700 nm. DETAILED DESCRIPTION
[0019] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.
[0020] Program Overview:
[0021] A scratch-resistant transparent decorative material comprises, by weight, 97.2 to 98.5 parts of polycarbonate, 1 to 2 parts of a scratch-resistant agent, 0.1 part of a hindered phenol antioxidant, 0.1 part of a phosphite antioxidant, and 0.3 to 0.6 parts of a surfactant.
[0022] The scratch-resistant agent is a mixture of low-molecular-weight micropowder and microcrystalline compounds and 10% of bio-based acid ester modified substances.
[0023] The hindered phenol antioxidant is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acrylonitrile, β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine.
[0024] The phosphite antioxidant is at least one of tris[2,4-di-tert-butylphenyl]phosphite and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.
[0025] A method for preparing a scratch-resistant transparent decorative material comprises the following steps:
[0026] Step 1: Add polycarbonate material, scratch resistance agent, surfactant, hindered phenol antioxidant and phosphite antioxidant into a high speed mixer and mix for 5 minutes;
[0027] Step 2: Add the obtained mixture into a twin-screw extruder for blending and granulation, the extruder temperature is 230-260° C., and the screw speed is 400 rpm;
[0028] Step 3: Dry the prepared material in a forced air drying oven at 100° C. for 4 h, and finally use it to prepare a transparent decorative strip.
[0029] Example 1
[0030] 98.5 parts of polycarbonate material, 1 part of scratch resistance agent, 0.3 parts of surfactant, 0.1 parts of hindered phenol antioxidant and 0.1 parts of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 230°C and the screw speed was 400 rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0031] The polycarbonate brand is PC-CH8225, and the manufacturer is Cangzhou Dahua;
[0032] The scratch-resistant agent is SD199 and the manufacturer is Shanghai Shengdian New Materials;
[0033] The surfactant brand is GHO4300, and the manufacturer is Difeiou Chemical;
[0034] The hindered phenol antioxidant is 1010, and the manufacturer is BASF Chemical;
[0035] The phosphite antioxidant is 168, and the manufacturer is BASF Chemicals.
[0036] Example 2
[0037] 97.2 parts of polycarbonate material, 2 parts of scratch resistance agent, 0.6 parts of surfactant, 0.1 parts of hindered phenol antioxidant and 0.1 parts of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 260°C and the screw speed was 400 rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0038] Comparative Example 1
[0039] 98.8 parts of polycarbonate material, 1 part of scratch resistance agent, 0.1 part of hindered phenol antioxidant and 0.1 part of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 260°C and the screw speed was 400 rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0040] Comparative Example 2
[0041] 97.8 parts of polycarbonate material, 2 parts of scratch resistance agent, 0.1 parts of hindered phenol antioxidant and 0.1 parts of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 260°C and the screw speed was 400 rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0042] Comparative Example 3
[0043] 99.5 parts of polycarbonate material, 0.3 parts of surfactant B, 0.1 parts of hindered phenol antioxidant and 0.1 parts of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 260°C and the screw speed was 400 rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0044] Comparative Example 4
[0045] 99.2 parts of polycarbonate material, 0.6 parts of surfactant, 0.1 parts of hindered phenol antioxidant and 0.1 parts of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 260°C and the screw speed was 400 rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0046] Comparative Example 5
[0047] 97.3 parts of polycarbonate material, 2.5 parts of silicone powder (brand: E525, manufacturer: Evonik Chemical), 0.1 parts of hindered phenol antioxidant and 0.1 parts of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 260°C and the screw speed was 400 rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0048] Comparative Example 6
[0049] 87.8 parts of polycarbonate material, 10 parts of polymethyl methacrylate (brand: CM205, manufacturer: Taiwan Chimei), 2 parts of compatibilizer (brand: HPC-1896, manufacturer: Shanghai Jiayirong), 0.1 parts of hindered phenol antioxidant and 0.1 parts of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 260°C and the screw speed was 400rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0050] Comparative Example 7
[0051] 99.8 parts of polycarbonate material, 0.1 parts of hindered phenol antioxidant and 0.1 parts of phosphite antioxidant were added to a high mixer and mixed for 5 minutes. The obtained mixture was added to a twin-screw extruder for blending and granulation. The extruder temperature was 260°C and the screw speed was 400 rpm / min. The prepared material was dried in a blast drying oven at 100°C for 4 hours and finally used to prepare transparent decorative strips.
[0052] Experimental Example Performance Characterization
[0053] The performance of the materials prepared in the above embodiments and comparative examples was characterized. The tensile strength and elongation at break were tested according to GB / T 1040-2022; the impact strength was tested according to GB / T 1843-2008; the flexural strength and modulus were tested according to GB / T 9341-2008; the melt index was tested according to GB / T3682-2018; the Rockwell hardness was tested according to GB / T3398-2008; the pencil hardness was tested according to GB / T 6739-2022; and the light transmittance and haze were tested according to GB / T2410-2008. The test results are shown in Table 1:
[0054] Table 1
[0055]
[0056] In Examples 1 and 2, different amounts of scratch resistant agent and surfactant were added for synergistic modification; in Comparative Examples 1 and 2, only different amounts of scratch resistant agent were added; in Comparative Examples 3 and 4, only different amounts of surfactant were added; in Comparative Example 5, conventional scratch resistant agent silicone powder was added; in Comparative Example 6, conventional hardening component polymethyl methacrylate resin was added; in Comparative Example 7, no scratch resistant agent and surfactant were added; as can be seen from the data in Table 1, compared with the comparative example, the materials of Examples 1-2 have better scratch resistance under the synergistic effect of the scratch resistant agent and the surfactant, and can ensure high transparency and relatively low haze.
[0057] In addition, the transmittance curve of the scratch-resistant material prepared in Example 1-2 in the wavelength range of 400 to 700 nm is as follows: Figure 1 As shown in the figure, it can be seen that the scratch-resistant material prepared in this embodiment has a light transmittance of more than 87% in the visible light wavelength range of 400nm to 700nm.
[0058] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A scratch-resistant transparent decorative material, characterized in that: The invention comprises, by weight, 97.2 to 98.5 parts of polycarbonate, 1 to 2 parts of scratch resistance agent, 0.3 to 0.6 parts of surfactant and 0.2 parts of antioxidant, wherein the antioxidant is a mixture of hindered phenol antioxidant and phosphite antioxidant.
2. The scratch-resistant transparent decorative material according to claim 1, characterized in that: The mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:(0.5-2).
3. The scratch-resistant transparent decorative material according to claim 2, characterized in that: The scratch-resistant agent is a mixture of low-molecular-weight micropowder and microcrystalline compounds and bio-based acid ester modified substances.
4. The scratch-resistant transparent decorative material according to claim 3, characterized in that: The added amount of the bio-based acid ester modification is 10%.
5. The scratch-resistant transparent decorative material according to claim 4, characterized in that: The hindered phenol antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acrylonitrile, β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate n-octadecyl ester, and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine, and the phosphite antioxidant is at least one of tris[2.4-di-tert-butylphenyl] phosphite and bis(2.4-di-tert-butylphenyl) pentaerythritol diphosphite.
6. The scratch-resistant transparent decorative material according to claim 5, characterized in that: The surfactant is a macromolecular stearate mixture.
7. A method for preparing a scratch-resistant transparent decorative material according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: adding polycarbonate material, scratch resistance agent, surfactant, hindered phenol antioxidant and phosphite antioxidant into a high speed mixer and mixing; Step 2, adding the obtained mixture into a twin-screw extruder for blending and granulation; Step 3: Dry the prepared material to obtain a scratch-resistant transparent decorative piece.
8. The method for preparing a scratch-resistant transparent decorative material according to claim 7, characterized in that: In step 1, the mixing time is 5 min; in step 2, the temperature of the twin-screw extruder is 230-260° C., and the screw speed is 400 rpm.
9. The method for preparing a scratch-resistant transparent decorative material according to claim 8, characterized in that: In step 3, the drying temperature is 100° C. and the drying time is 4 h.
Citation Information
Patent Citations
Transparent low-temperature-resistant scuffing-resistant polycarbonate composite material
CN106589880A
Scratch-resistant and high-transparent polycarbonate composite material and preparation method thereof
CN108976745A
High-transparency scratch-proof polycarbonate film
CN219727508U